MT-100, a human Tie2-agonistic antibody, improves penile neurovasculature in diabetic mice via the novel target Srpx2 - Fang-Yuan Liu; Young-Lai Cho; Fitri Rahma Fridayana; Lashkari Niloofar; Minh Nhat Vo; Yan Huang; Anita Limanjaya; Mi-Hye Kwon; Jiyeon Ock; Seon-Jin Lee; Guo Nan Yin; Nam-Kyung Lee; et al. (Experimental and Molecular Medicine)
Abstract Diabetes is an incurable, chronic disease that can lead to many complications, including angiopathy, peripheral neuropathy, and erectile dysfunction (ED). The angiopoietin-Tie2 signaling pathway plays a critical role in blood vessel development, formation, remodeling, and peripheral nerve regeneration. Therefore, strategies for activating the Tie2 signaling pathway have been developed as potential therapies for neurovascular diseases. Here, we developed a human Tie2-agonistic antibody (MT-100) that not only resists Ang-2 antagonism and activates Tie2 signaling but also regulates a novel target, sushi repeat-containing protein X-linked 2 (Srpx2). This regulation led to the survival of vascular and neuronal cells, a reduction in the production of reactive oxygen species (ROS), activation of the PI3K/AKT/eNOS signaling pathway, increased expression of neurotrophic factors, and ultimately alleviation of ED in diabetic mice. Our findings not only provide conclusive evidence that MT-100 is a promising therapeutic strategy for the treatment of diabetic ED but also suggest it has substantial clinical applications for other complications associated with diabetes.